Reduction of podocyte globotriaosylceramide content in adult male patients with Fabry disease with amenable GLA mutations following 6 months of migalastat treatment. Issue 11 (29th July 2017) - Mauer, Michael; Sokolovskiy, Alexey; Barth, Jay A; Castelli, Jeffrey P; Williams, Hadis N; Benjamin, Elfrida R; Najafian, Behzad
Abstract : Objective: Deficiency of α-galactosidase A (αGal-A) in Fabry disease leads to the accumulation mainly of globotriaosylceramide (GL3) in multiple renal cell types. Glomerular podocytes are relatively resistant to clearance of GL3 inclusions by enzyme replacement therapy (ERT). Migalastat, an orally bioavailable small molecule capable of chaperoning misfolded αGal-A to lysosomes, is approved in the European Union for the long-term treatment of patients with Fabry disease and amenable GLA (α-galactosidase A enzyme) mutations. We aimed to examine if migalastat reduces GL3 content of podocytes in Fabry disease. Methods and analysis: We compared paired renal biopsies of eight adult men with amenable Fabry disease mutations at baseline and after 6 months of treatment with 150 mg migalastat every other day using quantitative unbiased electron microscopic morphometric methods. Results: Migalastat treatment led to a reduction in mean total GL3 inclusion volume per podocyte in renal biopsies from baseline to 6 months. This reduction correlated precisely with reduced mean podocyte volume. There was also a direct relationship between reduction in podocyte foot process width and the reduction in mean total podocyte GL3 content following 6 months of migalastat treatment, suggestive of reduced podocyte injury. Conclusion: Migalastat treatment of 6 months duration in eight male patients with Fabry disease demonstrated effective GL3 clearance from the podocyte, an important and relatively ERT-resistant glomerular cell.